Solid electrolyte
A polymer-ceramic composite solid electrolyte enhances the stability and conductivity of lithium-air batteries, overcoming issues of mechanical fragility and aqueous solution instability, ensuring prolonged battery life and performance.
Patent Information
- Application Number
- JP2024193988
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2016-09-13
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing solid electrolytes for lithium-air batteries face challenges with low theoretical energy density, poor stability in aqueous solutions, and mechanical fragility, leading to safety issues and limited interface resistance in large-scale energy storage systems.
Development of a solid electrolyte composed of polymers such as polyvinyl acetal and polyvinyl acetate, combined with lithium or sodium salts and ceramic fillers, which form a flexible and stable ionic conductive film suitable for use in lithium-air batteries, even in aqueous environments.
The new solid electrolyte provides enhanced mechanical stability, improved conductivity, and extended cycle life in lithium-air batteries, maintaining performance in both neutral and acidic aqueous solutions, thereby addressing the limitations of previous materials.
Smart Images

Figure 2025016719000005 
Figure 2025016719000006 
Figure 2025016719000007
Abstract
Description
[Technical field]
[0001] The present invention relates to solid electrolytes. The solid electrolytes are useful as ionically conductive membrane dividers in batteries. In particular, the present invention relates to membrane dividers suitable for use in batteries in which the anode reacts with an aqueous solution, such as batteries having a lithium anode, particularly lithium-air batteries or lithium-sulfide batteries. However, the solid electrolytes are useful in other applications, including, but not limited to, sodium ion batteries and redox flow batteries. [Background technology]
[0002] The listing or discussion of a prior-published document in this specification should not necessarily be taken as an acknowledgement that the document is part of the state of the art or is common general knowledge.
[0003] A wide range of advanced energy storage systems rely heavily on the availability of high-rate lithium-ion conducting membranes that protect lithium or lithium alloy anodes from chemically reacting with the catholyte or cathode material. Rechargeable lithium-air batteries (LABs) promise very high specific energy and thus have the potential to replace currently available energy storage systems. Although LABs utilizing aqueous catholytes are characterized by somewhat lower theoretical energy density compared to conventional lithium-air batteries that rely on organic electrolytes, due to the high solubility of discharge products in the selected aqueous catholyte, combined with superior power performance, energy efficiency and volumetric energy density, they show a high potential to reach the theoretical limit in practical devices.
[0004] Aqueous and hybrid LABs allow for rapid lithium ion transport but require a fast ion conducting anode protection film that safely prevents chemical reactions between the lithium metal anode and the catholyte. The main class of solid electrolytes that have been successfully used as anode protection films in aqueous / hybrid LABs are NASICON type fast lithium ion conducting ceramics (Li-ion conducting ceramics, commonly referred to as "LAGPs"). 1+x Al xGe 2-x (PO4)3), and Li, also called "LTAP" 1+x Ti 2-x Al x (PO4)3). However, the usefulness of NASICON-type ceramics is limited by the difficulty of preparing them in suitable dimensions for large-scale energy storage systems, apart from the interfacial resistance at the electrolyte-electrode interface. Their brittleness also creates a risk of cracking if mechanically stressed during assembly or operation, constituting a major safety hazard in such systems.
[0005] Organic polymer electrolytes are easy and cheap to manufacture with large dimensions and a desired degree of flexibility to improve interfacial contact between the electrodes and electrolyte and to accommodate slight volume changes during cycling. Armand led the research on polymer-based ion-conducting materials in lithium batteries by investigating the use of solid electrolytes consisting of polyethylene oxide (PEO) and weakly coordinating Li salts (2008). Low-density polymer electrolytes are beneficial for the gravimetric energy density of energy storage systems, but so far, they have not been able to provide high mechanical stability and fast Li charge transfer. + A solid polymer electrolyte with a suitable combination of conductivity and chemical stability has not been found. Therefore, efforts have been made to combine ceramic and polymer electrolytes to produce hybrid inorganic-organic membranes consisting of a matrix and a filler, where the overall properties of the system depend on the properties of both the filler and the matrix as well as on the interactions between them.
[0006] Abraham, Li + A ceramic-polymer membrane consisting of conductive LTAP ceramic and a based gel electrolyte was fabricated, which showed high ionic conductivity, structural flexibility, and promising cyclability when used in Li / composite electrolyte / LiCoO2 batteries (2000).
[0007] Zhang reported that the introduction of LTAP into PEAP-based polymer electrolytes improved the electrical conductivity and interfacial stability under cycling while sandwiched between two lithium metal sheets (2002). However, although PEO-based electrolytes may seem to be potential electrolytes for lithium batteries, they are not suitable for aqueous or hybrid LABs due to their poor stability in aqueous solutions.
[0008] Safanama (2014) describes an inorganic-organic hybrid membrane containing LAGP and ion-conducting PEO. Because PEO swells by absorbing water from the catholyte, the PEO:PVDF:LiBF4 membrane is rapidly destroyed in practical applications using common catholytes such as LiOH or acidified LiCl solutions for aqueous Li-air batteries. Even under the mild phosphate buffer conditions described in Figure 6 of Safanama's paper (2014), the battery could only operate for about 3 hours.
[0009] Aetukuri is a single-layer Li 1.6 Al 0.5 Ti 0.95 Ta 0.5 (2015) fabricated a composite membrane by embedding (PO4)3 (LTAP) particles in a non-conductive cycloolefin polymer (COP) matrix. Each particle in a monolayer extended through the matrix to contact both the catholyte and the anolyte, and the matrix merely served to hold the LTAP particles in this arrangement. This membrane was used as an anode protective membrane in an organic Li-air battery with lithium iodide (LiI) added as a redox mediator on the cathode side. Fabrication of a membrane with a monolayer of LTAP particles extending through both sides of the support matrix appears to be difficult on an industrial scale.
[0010] Zhang, Li 1.4 Al 0.4 Ge 0.2 Ti 1.4A composite membrane of (PO4)3 and epoxy resin was prepared (2015). The composite membrane was heat-treated at a temperature of around 900°C to decompose the epoxy resin. The resulting ceramic membrane was used as an anode protection membrane in aqueous LAB. 5.3x10 -4 S cm -1 The ionic conductivity of LAB and its stability in contact with saturated aqueous LiCl were reported. However, LAB showed irregular charge and discharge curves, and the rather high overpotential and short life of the battery were not discussed.
[0011] Thus, there remains a need for solid electrolyte materials that are stable when in contact with aqueous electrolytes, while retaining electrical conductivity and flexibility. Summary of the Invention
[0012] Aspects and embodiments of the invention are presented in the following sections:
[0013] 1. A solid electrolyte comprising: a first polymer selected from one or more of the group consisting of polyvinyl acetal, polyvinyl acetate, and a copolymer comprising vinyl acetal and / or vinyl acetate units; and a dopant comprising a lithium salt or a sodium salt.
[0014] 2. The solid electrolyte of claim 1, wherein the polyvinyl acetal comprises units having the formula (I). [ka] wherein R1 and R2 are independently selected from hydrogen, alkyl or alkyl substituted with hydroxyl, thiol, amino, halo, nitro, alkoxy, thioalkyl, alkylamino, dialkylamino, carboxy, alkoxycarbonyl, carbamoyl, thiocarbamoyl, alkylcarbamoyl, alkylthiocarbamoyl, dialkylcarbamoyl, or dialkylthiocarbamoyl; and R3 is selected from hydrogen, alkyl or alkyl substituted with hydroxyl, thiol, amino, halo, nitro, alkoxy, thioalkyl, alkylamino, dialkylamino, carboxy, alkoxycarbonyl, carbamoyl, thiocarbamoyl, alkylcarbamoyl, alkylthiocarbamoyl, dialkylcarbamoyl, or dialkylthiocarbamoyl.
[0015] 3. The solid electrolyte of claim 2, wherein R1 and R2 are independently selected from hydrogen and alkyl.
[0016] 4. A solid electrolyte as described in paragraph 3, wherein R1 and R2 are both hydrogen.
[0017] 5. The solid electrolyte according to any one of items 2 to 4, wherein R3 is selected from hydrogen and alkyl.
[0018] 6. The solid electrolyte according to claim 5, wherein R3 is alkyl.
[0019] 7. The solid electrolyte according to claim 6, wherein R3 is methyl.
[0020] 8. The solid electrolyte according to paragraph 6, wherein R3 is propyl.
[0021] 9. The solid electrolyte according to paragraph 8, wherein R3 is n-propyl.
[0022] 10. The solid electrolyte according to paragraph 5, wherein R3 is hydrogen.
[0023] 11. The solid electrolyte according to any one of items 1 to 10, wherein the first polymer is a copolymer containing a vinyl acetal unit and a unit selected from one or more of the group consisting of a vinyl acetate unit, a vinyl alcohol unit, a (meth)acrylic acid unit, and a methyl (meth)acrylate unit.
[0024] 12. The solid electrolyte according to claim 11, wherein the first copolymer is a copolymer consisting of vinyl acetal units, vinyl acetate units and vinyl alcohol units.
[0025] 13. The solid electrolyte according to claim 12, wherein the copolymer has 78-84% vinyl acetate units, 15%-25% vinyl alcohol units, and 1-2% vinyl acetate units.
[0026] 14. The solid electrolyte according to claim 12, wherein the copolymer has 76-81% vinyl acetate units, 18-22% vinyl alcohol units, and 1-2% vinyl acetate units.
[0027] 15. The solid electrolyte of claim 12, wherein the copolymer has 78-79% vinyl acetate units, about 20% vinyl alcohol units, and 1-2% vinyl acetate units.
[0028] 16. The solid electrolyte according to claim 1, wherein the polyvinyl acetal is polyvinyl butyral.
[0029] 17. The solid electrolyte according to claim 1, wherein the polyvinyl acetal is polyvinyl acetal itself.
[0030] 18. The solid electrolyte according to claim 1, wherein the polyvinyl acetal is polyvinyl formal.
[0031] 19. The solid electrolyte may further comprise polyvinylidene difluoride (PVDF), polyvinyl alcohol, polyolefin resins, poly(propylene carbonate) polyester resins, tetrafluoroethylene, vinylidene difluoride-hexafluoropropylene copolymers, vinylidene difluoride-perfluorovinyl ether copolymers, vinylidene difluoride-tetrafluoroethylene copolymers, vinylidene difluoride-trifluoroethylene copolymers, vinylidene difluoride-fluoroethylene copolymers, difluoride 19. The solid electrolyte of any one of claims 1 to 18, comprising a second polymer selected from one or more of the group consisting of vinylidene difluoride-hexafluoroacetone copolymer, vinylidene difluoride-ethylene copolymer, vinylidene difluoride-propylene copolymer, vinylidene difluoride-trifluoropropylene copolymer, vinylidene difluoride-tetrafluoroethylene-hexafluoropropylene copolymer and vinylidene difluoride-ethylene-tetrafluoroethylene copolymer.
[0032] 20. The solid electrolyte of claim 19, wherein the second polymer is selected from one or more of the group consisting of polyvinylidene fluoride dimer (PVDF), polyvinyl alcohol, polyolefin-based resins, poly(propylene carbonate), and tetrafluoroethylene.
[0033] 21. The solid electrolyte according to claim 20, wherein the second polymer is a polyvinylidene fluoride dimer.
[0034] 22. The solid electrolyte according to any one of items 1 to 21, further comprising a plasticizer.
[0035] 23. The solid electrolyte according to item 22, wherein the plasticizer is selected from one or more of the group consisting of phthalate phosphate ester plasticizers, phosphoric acid esters, fatty acid esters, azelaic acid esters, sebacic acid esters, trimellitic acid esters, and polymeric plasticizers.
[0036] 24. The solid electrolyte of claim 23, wherein the plasticizer is a phthalate ester.
[0037] 25. The solid electrolyte according to paragraph 24, wherein the plasticizer is benzyl n-butyl phthalate.
[0038] 26. The solid electrolyte according to any one of items 1 to 25, wherein the dopant is a lithium salt.
[0039] 27. The solid electrolyte of claim 26, wherein the lithium salt is selected from one or more of the group consisting of lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl)imide, lithium bis(trifluoromethane)sulfonimide (Li[N(CF3SO2)2]), lithium(V) hexafluoroarsenate (LiAsF6), lithium bis(oxalatoborate), lithium nitrate (LiNO3), lithium chloride (LiCl), and lithium bromide (LiBr).
[0040] 28. The solid electrolyte of paragraph 27, wherein the lithium salt is selected from one or more of the group consisting of lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, and lithium chloride.
[0041] 29. The solid electrolyte according to claim 28, wherein the lithium salt is lithium tetrafluoroborate.
[0042] 30. The solid electrolyte according to claim 28, wherein the lithium salt is lithium chloride.
[0043] 31. The solid electrolyte according to any one of items 1 to 25, wherein the dopant is a sodium salt.
[0044] 32. The solid electrolyte of paragraph 31, wherein the sodium salt is selected from one or more of the group consisting of sodium nitrate (NaNO3), sodium perchlorate (NaClO4), sodium tetrafluoroborate (NaBF4), sodium hexafluorophosphate (NaPF6), sodium bis(trifluoromethanesulfonyl)imide, sodium bis(trifluoromethane)sulfonimide (Na[N(CF3SO2)2]) Na[N(CF3SO2)2], sodium hexafluoroarsenate(V) (NaAsF6), sodium bis(oxalatoborate), sodium halides, sodium thiocyanate (NaSCN), sodium pentacyanopropenide, sodium tetracyanopyrrolate, and sodium tricyanoimidazolate.
[0045] 33. The solid electrolyte according to any one of items 1 to 32, further comprising a lithium ion conductive ceramic or a sodium ion conductive ceramic.
[0046] 34. Lithium ion conductive ceramics include NASICON type ceramics, lithium filled garnet type oxides, LISICON type ceramics, perovskite type oxides, Li3PO4-Li4SiO4 pseudo binary system Li 3+x (P 1-x S x 34. The solid electrolyte of claim 33, wherein the solid electrolyte is selected from one or more of the group consisting of a solid solution in 04 and a lithium ion conducting oxyhalide glass.
[0047] 35. NASICON type ceramics have the general formula LiM2(PO4)3, where M is Ge, Ti, Hf, Sn and / or Zr; Li 1+x A x Ti2-x(PO4)3(LTAP) where A is a trivalent cation such as Al, Sc, Y, or La, or Li 1+x Al x Ge 2-x 35. The solid electrolyte according to claim 34, wherein the solid electrolyte is (PO4)3.
[0048] 36. Lithium-filled garnet-type oxides have the general formula Li7-3y-x La3Zr 2-x M1 y M2 x O 12 where M1 is a trivalent cation such as Al and / or Ga and / or M2 is a pentavalent cation such as Nb and / or Ta, and x≧0, y≦2; Li5La3M2O 12 , where M is Nb and / or Ta, with aliovalent dopants at the M site; Li6BaLa2Ta2O 12 Or Li 6.5 La 2.5 Ba 0.5 ZrTaO 12 35. The solid electrolyte according to claim 34, wherein
[0049] 37. LISICON type ceramics, Li 2+2x Zinc 1-x Ge4O 16 and Li 14 ZnGeO 16 35. The solid electrolyte according to claim 34, wherein the solid electrolyte is selected from one or more of the group consisting of:
[0050] 38. Perovskite oxides have the general formula Li 3x La (2 / 3)-x 35. The solid electrolyte according to claim 34, which is TiO3.
[0051] 39. The solid electrolyte of paragraph 34, wherein the oxyhalide glass has the general formula LiX-Li2O-B2O3, LiX-Li2O-SiO2, or LiX-Li2O-M2O, where X is F, Cl, Br, or I, and M is P, As, or V.
[0052] 40. The solid electrolyte of paragraph 35, wherein the ceramic is a NASICON type high rate lithium ion ceramic.
[0053] 41. Ceramics, Li 1+x Al x Ge 2-x 41. The solid electrolyte of claim 40, wherein the solid electrolyte is (PO4)3(LAGP).
[0054] 42. Ceramic is Li 1+x Al x Ge 2-x 42. The solid electrolyte according to claim 41, wherein (PO4)3 (x=0.5).
[0055] 43. The solid electrolyte of claim 33, wherein the sodium ion conducting ceramic oxide is selected from one or more of the group consisting of NaSICON structure oxides, beta alumina and beta''-alumina phases Na2O·nAl2O3 with 5≦n≦11, rare earth sodium silicates, and sodium ion conducting oxyhalide glasses.
[0056] 44. NASICON structure oxide has the general formula Na3Zr2Si2PO 12 , NaTi2(PO4)3, NaGe2(PO4)3, or Na 1+x [Sn x Ge 2-x 44. The solid electrolyte of claim 43, having a structure in which
[0057] 45. Rare earth sodium silicates have the general formula Na5MSi4O 12 44. The solid electrolyte according to item 43, having the formula:
[0058] 46. The solid electrolyte according to paragraph 43, wherein the sodium ion conducting oxyhalide glass is NaI-NaCl-Na2O-B2O3.
[0059] 47. The solid electrolyte of any one of claims 1 to 32, wherein the first polymer is present in an amount of 15 to 30% by weight.
[0060] 48. The solid electrolyte of any one of paragraphs 19 to 32, wherein the second polymer is present in an amount of 30 to 50% by weight.
[0061] 49. The solid electrolyte of any one of paragraphs 22 to 32, wherein the plasticizer is present in an amount of 10 to 25% by weight.
[0062] 50. A solid electrolyte according to any one of paragraphs 1 to 32, wherein the lithium or sodium salt is present in an amount of 15 to 30% by weight.
[0063] 51. The solid electrolyte according to any one of paragraphs 22 to 32, wherein the solid electrolyte comprises 10 to 25% by weight of a plasticizer, 15 to 30% by weight of a polyvinyl acetal, 15 to 30% by weight of a lithium or sodium salt, and 30 to 50% by weight of PvDF.
[0064] 52. The solid electrolyte of any one of paragraphs 22 to 32, wherein the solid electrolyte comprises 15 to 20 wt. % plasticizer, 20 to 25 wt. % polyvinyl acetal, 20 to 25 wt. % lithium or sodium salt, and 35 to 45 wt. % PvDF.
[0065] 53. The solid electrolyte of any one of paragraphs 22 to 32, wherein the solid electrolyte comprises 16 wt. % plasticizer, 21 wt. % polyvinyl acetal, 21 wt. % lithium or sodium salt, and 42 wt. % PvDF.
[0066] 54. The solid electrolyte of any one of paragraphs 33 to 46, wherein the ceramic is present at a level of 0.1% to 90% by weight, or 1% to 90% by weight, or 5% to 90% by weight, or 10% to 90% by weight, or 20% to 90% by weight, or 30% to 90% by weight, or 40% to 90% by weight, or 50% to 90% by weight.
[0067] 55. A solid electrolyte according to any one of paragraphs 33 to 46, wherein the ceramic is present at a level of 60% to 90% by weight.
[0068] 56. A solid electrolyte according to paragraph 55, comprising 60-90 wt. % of a fast lithium ion conducting ceramic, 1-5 wt. % of a plasticizer, 2-8 wt. % of a polyvinyl acetal, 2-8 wt. % of a lithium salt, and 4-15 wt. % of PvDF.
[0069] 57. A solid electrolyte according to paragraph 56, comprising 70-85 wt. % of a fast lithium ion conducting ceramic, 2-4 wt. % of a plasticizer, 3-6 wt. % of a polyvinyl acetal, 3-6 wt. % of a lithium salt, and 4-15 wt. % of PvDF.
[0070] 58. A solid electrolyte according to paragraph 57, comprising 78-82 wt. % of a fast lithium ion conducting ceramic, 2-4 wt. % of a plasticizer, 3-5 wt. % of a polyvinyl acetal, 3-6 wt. % of a lithium salt, and 7-10 wt. % of PvDF.
[0071] 59. A solid electrolyte according to paragraph 55, comprising 60-90 wt. % of a fast lithium ion conducting ceramic, 1-5 wt. % of a plasticizer, 3-6 wt. % of a polyvinyl acetal, 2-8 wt. % of a lithium salt, and 4-15 wt. % of PvDF.
[0072] 60. A solid electrolyte according to paragraph 59, comprising 70-85 wt.% of a fast lithium ion conducting ceramic, 2-4 wt.% of a plasticizer, 3-6 wt.% of a polyvinyl acetal, 3-6 wt.% of a lithium salt, and 6-12 wt.% of PvDF.
[0073] 61. A solid electrolyte according to paragraph 60, comprising 78-82 wt.% of a fast lithium ion conducting ceramic, 2-4 wt.% of a plasticizer, 3-5 wt.% of a polyvinyl acetal, 3-6 wt.% of a lithium salt, and 7-10 wt.% of PvDF.
[0074] 62. The solid electrolyte according to paragraph 55, comprising 60-90% by weight LAGP, 1-5% by weight benzyl butyl phthalate, 2-8% by weight polyvinyl butyral, 2-8% by weight LiBF4, and 4-15% by weight PVDF.
[0075] 63. The solid electrolyte according to paragraph 55, comprising 70-85% by weight LAGP, 2-4% by weight benzyl butyl phthalate, 3-6% by weight polyvinyl butyral, 3-6% by weight LiBF4, and 6-12% by weight PVDF.
[0076] 64. A solid electrolyte according to paragraph 63, comprising 78-82 wt. % LAGP, 2-4 wt. % benzyl butyl phthalate, 3-5 wt. % polyvinyl butyral, 3-5 wt. % LiBF4, and 7-10 wt. % PVDF.
[0077] 65. The solid electrolyte of paragraph 64, comprising 81 wt. % LAGP, 3 wt. % benzyl butyl phthalate, 4 wt. % polyvinyl butyral, 4 wt. % LiBF4, and 8 wt. % PVDF.
[0078] 66. A solid electrolyte according to paragraph 55, comprising 60-90 wt. % of garnet-related type Ta-doped lithium lanthanum zirconate, 2-8 wt. % of a plasticizer, 2-8 wt. % of a polyvinyl acetal, 2-8 wt. % of a lithium salt, and 4-15 wt. % of PVDF.
[0079] 67. A solid electrolyte according to paragraph 55, comprising 60-90 wt. % of garnet-related type Nb-doped lithium lanthanum zirconate, 2-8 wt. % of a plasticizer, 2-8 wt. % of polyvinyl acetal, 2-8 wt. % of a lithium salt, and 4-15 wt. % of PVDF.
[0080] 68. A solid electrolyte according to paragraph 55, comprising 60-90% by weight of garnet-related type Al-doped lithium lanthanum zirconate, 2-8% by weight of a plasticizer, 2-8% by weight of polyvinyl acetal, 2-8% by weight of a lithium salt, and 4-15% by weight of PVDF.
[0081] 69. A solid electrolyte according to paragraph 55, comprising 60-90 wt. % of garnet-related type Al and Ga co-doped lithium lanthanum zirconate, 2-8 wt. % of a plasticizer, 2-8 wt. % of a polyvinyl acetal, 2-8 wt. % of a lithium salt, and 4-15 wt. % of PVDF.
[0082] 70. A solid electrolyte according to paragraph 55, comprising 60-90 wt. % of garnet-related type lithium lanthanum zirconate co-doped with Ta and Ga, 2-8 wt. % of a plasticizer, 2-8 wt. % of a polyvinyl acetal, 2-8 wt. % of a lithium salt, and 4-15 wt. % of PVDF.
[0083] 71. A solid electrolyte as described in paragraph 70, comprising 80 wt. % garnet-related type Ta and Ga co-doped lithium lanthanum zirconate, 2 wt. % benzyl butyl phthalate, 4 wt. % polyvinyl butyral, 6 wt. % lithium chloride, and 8 wt. % PVDF.
[0084] 72. A solid electrolyte as described in paragraph 70, comprising 82 wt. % garnet-related type Ta and Ga co-doped lithium lanthanum zirconate, 4 wt. % polyvinyl butyral, 6 wt. % lithium chloride, and 8 wt. % PVDF.
[0085] 73. An ion-conducting membrane divider for use in a battery comprising the solid electrolyte according to any one of paragraphs 1 to 72.
[0086] 74. A battery comprising an anode, a cathode, a catholyte, and optionally an anolyte, wherein an ionically conductive membrane divider according to paragraph 73 separates the catholyte from the anode.
[0087] 75. The battery of paragraph 74, wherein the battery has a lithium anode.
[0088] 76. The battery of paragraph 75, wherein the battery is a lithium air battery or a lithium sulfide battery.
[0089] 77. a) preparing a solid electrolyte according to any one of items 1 to 72; and b) A method of making an ion-conducting membrane divider suitable for use in a battery, comprising forming a solid electrolyte into a membrane.
[0090] 78. The method of claim 77, wherein a slurry containing the solid electrolyte is formed into a membrane by tape casting.
[0091] 79. The method of claim 77, wherein the solid electrolyte is formed into a membrane by hot pressing. [Brief description of the drawings]
[0092] [Figure 1] FIG. 1 shows (a) the Rietveld refined XRD patterns for a LAGP pellet annealed at 850° C. for 2 h; (+) observed, (-) calculated and difference (wRp=6%); vertical bars corresponding to calculated Braggs indicate LAGP (top), GeO2 (middle) and Li4P2O4 (bottom), and (b) room temperature Nyquist plots of impedance for the LAGP pellet. [Diagram 2] 2 is an Arrhenius plot of the total conductivity of the polymer electrolyte according to the invention. The room temperature conductivity of the pure polymer phase is σtotal = 3x10-6S cm-1. [Diagram 3] FIG. 3 shows the DSC measurements (30° C. to 250° C.) of a hybrid LAGP polymer membrane according to the present invention after immersion in deionized water for about one week. [Figure 4] 4 shows (a) room temperature Nyquist plots (gold sputter; data fitted using FRA software and an equivalent circuit for R(RQ)Q) of a hybrid LAGP polymer film according to the invention, and (b) Rietveld refined powder XRD patterns for a hybrid film according to the invention. Vertical bars correspond to Bragg reflections calculated from the R-3c model for LAGP (top) and the P3121 model for GeO2 (bottom). [Diagram 5] Figure 5. (a) Room temperature Nyquist plots of impedance of hybrid films with garnet-type Ta, Ga co-doped Li6.75La3Zr1.75Ta0.25O12Ga0.05 as ceramic filler, (b) effect of different doping salts on the conductivity of hybrid films with garnet-type filler (triangles: 4% LiBF4, squares: 4% LiTFSi, circles: 4% LiCl). [Figure 6] FIG. 6 shows XRD patterns of a hybrid inorganic-organic LAGP polymer film according to the present invention before and after immersion in (a) a weakly acidic LiCl aqueous solution (10 M, pH≈6) and (b) acidified LiCl (10 M, pH≈2). [Figure 7] FIG. 7 shows the room temperature Nyquist plot of impedance of a hybrid LAGP:polymer film according to the invention (without gold sputtering) as a function of immersion time. [Figure 8] FIG. 8 shows SEM images of a hybrid LAGP polymer membrane according to the present invention (a) before immersion, (b) after 7 days of immersion, (c) after 14 days of immersion, and (d) after 6 months of immersion. [Figure 9] FIG. 9 shows the charge / discharge profiles of a Li-air battery using a hybrid LAGP polymer membrane according to the present invention with (a) neutral LiCl (10 M), (b) acidified LiCl (10 M) under a constant current density of 0.03 mA cm (≈100 mA / gc) in catholyte, and (c) cell overpotential versus cycle number for the hybrid and PEO-based membranes. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0093] The present invention relates to a solid electrolyte suitable for use in batteries comprising a first polymer selected from one or more of the group consisting of polyvinyl acetal, polyvinyl acetate, and copolymers comprising vinyl acetal and / or vinyl acetate units doped with lithium or sodium salts. In particular, the present invention relates to ion-conducting membrane dividers made from this material, and to a scalable method of making such membranes. Such membrane dividers are mechanically flexible and very stable. The membrane dividers can be used in batteries comprising anodes that would be degraded by contact with aqueous electrolytes to protect the anode. In particular, they can be used as anode protection membranes when placed between the anode (or the anode compartment containing an organic anolyte) and the liquid catholyte or electrolyte in lithium-air batteries. However, the solid electrolytes can also be used in other applications, such as all-solid-state lithium-ion batteries, and sodium-ion batteries and redox flow batteries.
[0094] As used herein, the term "solid electrolyte" refers to a solid with highly mobile ions. These materials are also known as "fast ion conductors" and "superionic conductors". Fast ion conductors are intermediate in properties between crystalline solids with ordered structure with immobile ions and liquid electrolytes with no ordered structure and completely mobile ions. These materials exhibit very high values of ionic conductivity due to the rapid diffusion of ionic species through the lattice. In many cases the lattice is formed by immobile counterions, but salts dissolved in polymers or dispersed in organic matrices can also act as fast ion conductors.
[0095] As used herein, a "dopant," also called a "doping agent," is a material that is inserted into a material to change the electrical or optical properties of the material. The material is said to be "doped." As used herein, polymers can be doped to increase electrical conductivity to produce solid electrolytes by introducing salts.
[0096] As used herein, the term "polyvinyl acetal" refers to a polymer that contains multiple vinyl acetal units in the polymer backbone. In particular, the term refers to a polymer that contains multiple 1,3-dioxane moieties in the polymer backbone. Typically, the 1,3-dioxane moieties are attached to adjacent carbon atoms at the 4- and 6-positions of the backbone. Polyvinyl acetals are prepared by modification of polyvinyl acetate. As a first step, polyvinyl acetate is hydrolyzed to form polyvinyl alcohol. Polyvinyl alcohol is then modified by reaction with an aldehyde to obtain polyvinyl acetal. However, neither reaction proceeds to completion. Thus, in addition to the vinyl acetal groups, polyvinyl acetals contain units derived from vinyl acetate and / or vinyl alcohol. For example, polyvinyl butyral is prepared from polyvinyl alcohol by reaction with butyraldehyde, but contains units derived from vinyl acetate and / or vinyl alcohol in addition to vinyl butyral units.
[0097] As used herein, the term "polyvinyl acetal itself" refers to the specific reaction product of polyvinyl alcohol with acetaldehyde (which may contain polyvinyl acetate residues, as discussed in the definition of "polyvinyl acetal" above), which at the same time shares the same name as an entire class of polymers.
[0098] As used herein, unless otherwise specified, the term "alkyl" refers to an unsubstituted, branched or straight chain, monovalent saturated aliphatic hydrocarbon moiety of 1 to 20 carbon atoms. This term includes, but is not limited to, moieties such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, and the various isomers of each moiety when there are three or more carbons. For example, butyl includes isobutyl, n-butyl, and tert-butyl. Propyl includes n-propyl and isopropyl. Alkyl moieties generally have a C 1-6 It is an alkyl.
[0099] As used herein, the term "alkoxy" refers to the group -O-R', where R' is alkyl.
[0100] As used herein, the term "thioalkyl" refers to the group -S-R', where R' is alkyl.
[0101] As used herein, the term "carboxy" or "carboxylic acid" refers to the group -C(O)OH.
[0102] As used herein, the term "alkoxycarbonyl" refers to the group -C(O)OR', where R' is alkyl.
[0103] As used herein, the term "carbamoyl" refers to the group -C(O)NR'R, where R and R' are independently hydrogen or alkyl; for example, when R is hydrogen and R' is alkyl, the group is alkylcarbamoyl, and when R and R'S are each alkyl, the group is dialkylcarbamoyl.
[0104] As used herein, the term "thiocarbamoyl" refers to the group -C(S)NR'R where R and R' are independently hydrogen or alkyl, e.g., when R is hydrogen and R' is alkyl the group is alkylthiocarbamoyl, and when R and R' are each alkyl the group is dialkylthiocarbamoyl.
[0105] As used herein, the term "halo" refers to fluoro, bromo, chloro and iodo.
[0106] As used herein, the term "polymer" refers to a homopolymer or a copolymer.
[0107] As used herein, the term "homopolymer" refers to a polymer formed from a single type of monomer. Nevertheless, it will be understood that homopolymers, especially when they are prepared by modification of another polymer, may contain some units other than those derived from that monomer due to side reactions or incomplete reaction. For example, polyvinyl alcohol is produced by hydrolysis of polyvinyl acetate, and it cannot be guaranteed that all side chains are hydrolyzed. Polyvinyl acetal is produced by reaction of polyvinyl alcohol with an aldehyde, and not all alcohol groups may react. Thus, polyvinyl acetal homopolymers may contain small amounts of both polyvinyl alcohol and polyvinyl acetate residues.
[0108] As used herein with respect to a polymer, the term "unit" or its plural "units" refers to the portion of a monomer that remains after polymerization. A "unit" may be modified in a post-polymerization reaction.
[0109] As used herein, the term "copolymer" refers to a polymer formed from more than a single type of monomer, and includes various forms of copolymers such as alternating copolymers, block copolymers, and graft copolymers.
[0110] In one embodiment, the polyvinyl acetal comprises units having the structure shown in formula I: [ka] wherein R1 and R2 are independently hydrogen, alkyl and alkyl substituted with hydroxyl, thiol, amino, halo, nitro, alkoxy, thioalkyl, alkylamino, dialkylamino, carboxy, alkoxycarbonyl, carbamoyl, thiocarbamoyl, alkylcarbamoyl, alkylthiocarbamoyl, dialkylcarbamoyl or dialkylthiocarbamoyl, typically C 1-6 alkyl, and R3 is hydrogen, alkyl and alkyl substituted with hydroxyl, thiol, amino, halo, nitro, alkoxy, thioalkyl, alkylamino, dialkylamino, carboxy, alkoxycarbonyl, carbamoyl, thiocarbamoyl, alkylcarbamoyl, alkylthiocarbamoyl, dialkylcarbamoyl or dialkylthiocarbamoyl, typically C 1-6 is selected from alkyl.
[0111] In one embodiment, R1 and R2 are independently selected from hydrogen and alkyl.
[0112] In one embodiment, R1 and R2 are each hydrogen.
[0113] In one embodiment, R3 is selected from hydrogen and alkyl.
[0114] In one embodiment, R3 is alkyl.
[0115] In one embodiment, R3 is methyl.
[0116] In one embodiment, R3 is propyl.
[0117] In one embodiment, R3 is n-propyl.
[0118] In one embodiment, R3 is hydrogen.
[0119] In one embodiment, the first polymer is polyvinyl butyral, available, for example, from Eastman Chemical under the name BUTVAR.
[0120] In one embodiment, the first polymer is itself polyvinyl acetal, a polymer formerly sold by Monsanto under the name ALVAR.
[0121] In one embodiment, the first polymer is polyvinylformyl, originally sold under the name FORMVAR by Monsanto Chemical Company, and now sold as VINYLEC by JNC Corporation.
[0122] In one embodiment, the first polymer is a copolymer having vinyl acetal units and units derived from the group consisting of vinyl acetate, vinyl alcohol, (meth)acrylic acid, and methyl (meth)acrylate.
[0123] In one embodiment, the copolymer has vinyl acetal units and units derived from vinyl acetate and / or vinyl alcohol.
[0124] In one embodiment, the copolymer comprises 73-84% vinyl acetate units, 15-25% vinyl alcohol units, and 1-2% vinyl acetate units.
[0125] In one embodiment, the copolymer comprises 76-81% vinyl acetate units, 18%-22% vinyl alcohol units, and 1-2% vinyl acetate units.
[0126] In one embodiment, the copolymer comprises 78-79% vinyl acetate units, about 20% vinyl alcohol units, and 1-2% vinyl acetate units.
[0127] In one embodiment, the solid electrolyte further comprises a second polymer selected from one or more of the group consisting of polyvinylidene difluoride dimer (PVDF), polyvinyl alcohol, polyolefin-based resins, poly(propylene carbonate), polyester-based resins, tetrafluoroethylene, vinylidene difluoride-hexafluoropropylene copolymers, vinylidene difluoride-perfluorovinyl ether copolymers, vinylidene difluoride-tetrafluoroethylene copolymers, vinylidene difluoride-trifluoroethylene copolymers, vinylidene difluoride-fluoroethylene copolymers, vinylidene difluoride-hexafluoroacetone copolymers, vinylidene difluoride-ethylene copolymers, vinylidene difluoride-propylene copolymers, vinylidene difluoride-trifluoropropylene copolymers, vinylidene difluoride-tetrafluoroethylene-hexafluoropropylene copolymers, and vinylidene difluoride-ethylene-tetrafluoroethylene copolymers. Examples of the polyolefin resin include polyethylene and polypropylene, and examples of the polyester resin include polyethylene terephthalate and polybutylene terephthalate.
[0128] In one embodiment, the second polymer is selected from one or more of the group consisting of polyvinylidene fluoride dimer (PVDF), polyvinyl alcohol, polyolefin-based resin, poly(propylene carbonate), tetrafluoroethylene. Typically, the polyolefin-based resin is polyethylene.
[0129] In one embodiment, the second polymer is polyvinylidene difluoride (PVDF).
[0130] In one embodiment, the solid electrolyte further comprises an inactive component selected from one or more of the group consisting of a filler, an antioxidant, a colorant, an anti-fouling agent, and a dispersant.
[0131] In one embodiment, the solid electrolyte further comprises a plasticizer.
[0132] In one embodiment, the plasticizer is selected from one or more of the group consisting of phthalate esters, phosphate ester plasticizers, phosphoric acid esters, fatty acid esters, azelaic acid esters, sebacic acid esters, trimellitic acid esters, and polymeric plasticizers. In one embodiment, a phthalate ester is used. In one embodiment, the plasticizer is benzyl n-butyl phthalate.
[0133] Solid polymer electrolytes for lithium and sodium ion batteries contain low lattice energy lithium and sodium salts as dopants for the polymer or polymer blend.
[0134] In one embodiment, the dopant is a lithium salt.
[0135] In one embodiment, the dopant is selected from one or more of the group consisting of lithium perchlorate (LiClO), lithium tetrafluoroborate (LiBF), lithium hexafluorophosphate (LiPF), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(trifluoromethane)sulfonimide (Li[N(CFSO)]), lithium(V) hexafluoroarsenate (LiAsF), lithium bis(oxalatoborate) ("LiBOB"), lithium nitrate (LiNO), lithium chloride (LiCl), and lithium bromide (LiBr).
[0136] In one embodiment, the dopant is lithium tetrafluoroborate (LiBF4).
[0137] In one embodiment, the dopant is a sodium salt.
[0138] In one embodiment, the dopant is selected from one or more of the group consisting of sodium nitrate (NaNO3), sodium perchlorate (NaClO4), sodium tetrafluoroborate (NaBF4), sodium hexafluorophosphate (NaPF6), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium bis(trifluoromethane)sulfonimide (Na[N(CF3SO2)2]), sodium hexafluoroarsenate(V) (NaAsF6), sodium bis(oxalatoborate) ("NaBOB"), sodium halides (NaX) where X = Cl, Br, or I, sodium thiocyanate (NaSCN), sodium pentacyanopropene (NaPCPI), sodium tetracyanopyrrolate (NaTCP), and sodium tricyanoimidazolate (NaTIM).
[0139] The solid electrolyte may further comprise a ceramic. Any suitable ion-conducting ceramic may be used.
[0140] In one embodiment, the solid electrolyte further comprises a lithium ion conducting ceramic or a sodium ion conducting ceramic.
[0141] In one embodiment, the lithium ion conducting ceramic is selected from the group consisting of NASICON type ceramics, lithium loaded garnet type oxides, LISICON type ceramics, perovskite type oxides, Li3PO4-Li4SiO4 pseudobinary Li 3+x (P 1-x S x )O4 solid solutions and lithium ion conducting oxyhalide glasses.
[0142] In one embodiment, the NASICON type ceramic has the general formula LiM2(PO4)3, where M is Ge, Ti, Hf, Sn, or Zr; 1+x A x Ti 2-x(PO4)3(LTAP), where A is a trivalent cation such as Al, Sc, Y and / or La; or Li 1+x Al x Ge 2-x (PO4)3.
[0143] In one embodiment, the lithium-filled garnet-type oxide has the general formula Li 7-3y-x La3Zr 2-x M 1 y M 2 x O 12 So, M. 1 is Al, Ga and / or M 2 Trivalent cations such as M 2 is a pentavalent cation such as Nb and / or Ta, x≧0, y≦2; Li5La3M 2 O 12 where M is Nb and / or Ta, and has an aliovalent dopant at the M site; Li6BaLa2Ta2O 12 ; or Li 6.5 La 2.5 Ba 0.5 ZrTaO 12 It is.
[0144] In one embodiment, the LISICON type ceramic is Li 2+2x Zinc 1-x Ge4O 16 and Li 14 ZnGeO 16 and wherein the aryl group is selected from one or more of the group consisting of:
[0145] In one embodiment, the perovskite oxide has the general formula Li 3x La (2 / 3)-x It is TiO3.
[0146] In one embodiment, the oxyhalide glass has the general formula LiX-Li2O-B2O3, LiX-Li2O-SiO2, or LiX-Li2O-M2O5, where X is F, Cl, Br, or I, and M is P, As, or V.
[0147] In one embodiment, the ceramic is a NASICON type high rate lithium ion ceramic.
[0148] In one embodiment, the ceramic is LAGP.
[0149] In one embodiment, the ceramic is Li 1+x Al x Ge 2-x (PO4)3(x=0.5) glass.
[0150] In one embodiment, the sodium ion conducting ceramic is selected from one or more of the group consisting of NaSICON structured oxides, beta alumina and β″-alumina phases Na2O·nAl2O3 5≦n≦11, rare earth sodium silicates, and sodium ion conducting oxyhalide glasses.
[0151] In one embodiment, the NaSICON structure oxide has the general formula Na3Zr2Si2PO 12 , NaTi2(PO4)3, NaGe2(PO4)3 or Na 1+x [Sn x Ge 2-x (PO4)3].
[0152] In one embodiment, the sodium rare earth silicate has the general formula NaMSiO 12 where M is Y, Sc, Lu and / or any trivalent rare earth cation.
[0153] In one embodiment, the sodium ion conducting oxyhalide glass is NaI-NaCl-Na2O-B2O3.
[0154] A fast ion conducting ceramic may or may not be present. If present, electrical conductivity is increased by several orders of magnitude and mechanical stability, including stability against intrusion by lithium dendrites, is significantly increased. If present, the ceramic typically comprises 60 to 90% by weight of the composition, but may be present in an amount of 0.1% to 90% by weight.
[0155] In one embodiment where no ceramic is present, the first polymer can be present in an amount of 15 to 30 wt%. Alternatively, the first polymer can be present in an amount of 20 to 25 wt%. Typically, the first polymer is present in an amount of 21 wt%.
[0156] In one embodiment where no ceramic is present, the second polymer can be present in an amount of 30 to 50 wt%. Alternatively, the second polymer can be present in an amount of 35 to 45 wt%. Typically, the second polymer is present in an amount of 42 wt%.
[0157] In one embodiment where no ceramic is present, the plasticizer may be present in an amount of 10 to 25 wt%. Alternatively, the plasticizer may be present in an amount of 15 to 20 wt%. Typically, the plasticizer is present in an amount of 16 wt%.
[0158] In the absence of a ceramic, any ion may be used to carry charge across a suitably doped membrane, as it does not have to be compatible with the ceramic. Thus, any dopant salt that dissolves in the polymer in the appropriate amount can be used. The salt is typically present in an amount of 1-40% by weight.
[0159] Typically, the salt is a sodium or lithium salt. In one embodiment in which no ceramic is present, the sodium or lithium salt may be present in an amount of 15 to 30 wt%. Alternatively, the sodium or lithium salt may be present in an amount of 20 to 25 wt%. Typically, the sodium or lithium salt is present in an amount of 21 wt%.
[0160] In one embodiment, the solid electrolyte in the absence of ceramic comprises 10-25 wt.% plasticizer, 15-30 wt.% polyvinyl acetal, 15-30 wt.% lithium or sodium salt, and 30-50 wt.% PvDF.
[0161] In one embodiment, the solid electrolyte in the absence of ceramic comprises 15-20 wt. % plasticizer, 20-25 wt. % polyvinyl acetal, 20-25 wt. % lithium or sodium salt, and 35-45 wt. % PvDF.
[0162] In one embodiment, the solid electrolyte in the absence of ceramic comprises 16 wt. % plasticizer, 21 wt. % polyvinyl acetal, 21 wt. % lithium or sodium salt, and 42 wt. % PvDF.
[0163] Typically, the ceramic is present to enhance electrical conductivity and mechanical strength. The presence of the ceramic enhances electrical conductivity at any level, for example, from 0.1% to 90% by weight, or from 1% to 90% by weight, or from 5% to 90% by weight, or from 10% to 90% by weight, or from 20% to 90% by weight, or from 30% to 90% by weight, or from 40% to 90% by weight, or from 50% to 90% by weight, typically from 60% to 90% by weight. The amount of ceramic present will depend on the purpose for which the article made from the solid electrolyte is to be placed, the nature of the ceramic, and the other components of the solid electrolyte.
[0164] When the ceramic is present in an amount of 60 to 90 weight percent, the first polymer is typically present in an amount of 2 to 8 weight percent. In one embodiment, the first polymer is present in an amount of 3 to 6 weight percent. In one embodiment, the first polymer is present in an amount of 3 to 5 weight percent.
[0165] When the ceramic is present in an amount of 60 to 90 weight percent, the second polymer is typically present in an amount of 4 to 15 weight percent. In one embodiment, the second polymer is present in an amount of 6 to 12 weight percent. In one embodiment, the second polymer is present in an amount of 7 to 10 weight percent.
[0166] When the ceramic is present in an amount of 60 to 90% by weight, the plasticizer is typically present in an amount of 1 to 5% by weight. In one embodiment, the plasticizer is present in an amount of 2 to 4% by weight.
[0167] When the ceramic is present in an amount of 60 to 90% by weight, either the sodium or lithium salt is typically present in an amount of 2 to 10% by weight, in one embodiment the sodium or lithium salt is present in an amount of 3 to 6% by weight.
[0168] In one embodiment, the solid electrolyte comprises 60-90 wt. % of a fast lithium ion conducting ceramic, 1-5 wt. % of a plasticizer, 2-8 wt. % of a polyvinyl acetal, 2-10 wt. % of a lithium salt, and 4-15 wt. % of PvDF.
[0169] In one embodiment, the solid electrolyte comprises 70-85 wt.% of a fast lithium ion conducting ceramic, 2-4 wt.% of a plasticizer, 3-6 wt.% of a polyvinyl acetal, 3-6 wt.% of a lithium salt, 3-6 wt.% of a lithium salt, and 6-12 wt.% of PvDF.
[0170] In one embodiment, the solid electrolyte comprises 78-82 wt. % of a high rate lithium ion conducting ceramic, 2-4 wt. % of a plasticizer, 3-5 wt. % of a polyvinyl acetal, 3-6 wt. % of a lithium salt, and 7-10 wt. % of PvDF.
[0171] In one embodiment, the solid electrolyte comprises 60-90 wt. % of a fast sodium ion conducting ceramic, 1-5 wt. % of a plasticizer, 2-8 wt. % of a polyvinyl acetal, 2-10 wt. % of a sodium salt, and 4-15 wt. % of PvDF.
[0172] In one embodiment, the solid electrolyte comprises 70-85 wt. % of a fast sodium ion conducting ceramic, 2-4 wt. % of a plasticizer, 3-6 wt. % of a polyvinyl acetal, 3-6 wt. % of a sodium salt, and 6-12 wt. % of PvDF.
[0173] In one embodiment, the solid electrolyte comprises 78-82 wt. % of a fast sodium ion conducting ceramic, 2-4 wt. % of a plasticizer, 3-5 wt. % of a polyvinyl acetal, 3-6 wt. % of a sodium salt, and 7-10 wt. % of PvDF.
[0174] In one embodiment, the solid electrolyte comprises 60-90 wt. % LAGP, 1-5 wt. % benzyl butyl phthalate, 2-8 wt. % polyvinyl butyral, 2-10 wt. % LiBF4, and 4-15 wt. % PVDF.
[0175] In one embodiment, the solid electrolyte comprises 70-85 wt. % LAGP, 2-4 wt. % benzyl butyl phthalate, 3-6 wt. % polyvinyl butyral, 3-6 wt. % LiBF4, and 6-12 wt. % PVDF.
[0176] In one embodiment, the solid electrolyte comprises 78-82 wt. % LAGP, 2-4 wt. % benzyl butyl phthalate, 3-5 wt. % polyvinyl butyral, 3-5 wt. % LiBF4, and 7-10 wt. % PVDF.
[0177] In one embodiment, the solid electrolyte comprises 81 wt. % LAGP, 3 wt. % benzyl butyl phthalate, 4 wt. % polyvinyl butyral, 4 wt. % LiBF4, and 8 wt. % PVDF.
[0178] In one embodiment, the solid electrolyte comprises 60-90 wt. % of garnet-related type Ta-doped lithium lanthanum zirconate, 2-8 wt. % of a plasticizer, 2-8 wt. % of polyvinyl acetal, 2-8 wt. % of a lithium salt, and 4-15 wt. % of PVDF.
[0179] In one embodiment, the solid electrolyte comprises 60-90 wt. % of garnet-related type Nb-doped lithium lanthanum zirconate, 2-8 wt. % of a plasticizer, 2-8 wt. % of polyvinyl acetal, 2-8 wt. % of a lithium salt, and 4-15 wt. % of PVDF.
[0180] In one embodiment, the solid electrolyte comprises 60-90 wt. % garnet-related type Al-doped lithium lanthanum zirconate, 2-8 wt. % plasticizer, 2-8 wt. % polyvinyl acetal, 2-8 wt. % lithium salt, and 4-15 wt. % PVDF.
[0181] In one embodiment, the solid electrolyte comprises 60-90 wt. % garnet-related type Al and Ga co-doped lithium lanthanum zirconate, 2-8 wt. % plasticizer, 2-8 wt. % polyvinyl acetal, 2-8 wt. % lithium salt, and 4-15 wt. % PVDF.
[0182] In one embodiment, the solid electrolyte is 60-90 wt. % of garnet-related Ta and Ga co-doped lithium lanthanum zirconate, 2-8 wt. % of a plasticizer, 2-8 wt. % of polyvinyl acetal, 2-8 wt. % of a lithium salt, and 4-15 wt. % of PVDF.
[0183] In one embodiment, the solid electrolyte comprises 80 wt. % garnet-related type Ta and Ga co-doped lithium lanthanum zirconate, 2 wt. % benzyl butyl phthalate, 4 wt. % polyvinyl butyral, 6 wt. % LiCl, and 8 wt. % PVDF.
[0184] In one embodiment, the solid electrolyte comprises 82 wt. % garnet-related type Ta and Ga co-doped lithium lanthanum zirconate, 4 wt. % polyvinyl butyral, 6 wt. % LiCl, and 8 wt. % PVDF.
[0185] A full cell battery includes an anode, a cathode, a catholyte, and optionally an anolyte, and an ion-conducting membrane divider, if present, that separates the catholyte from the anolyte, and the membrane separator is a divider. The nature of the anode and cathode depend on the type of battery. Selection of suitable materials for the anode and cathode in a battery is well understood by those skilled in the art.
[0186] As an example, in a lithium-ion battery, the cathode is typically made of an inserted lithium compound. Examples of electrode materials include lithium cobaltate, lithium nickel oxide, lithium nickel cobalt oxide, spinel-type lithium manganese oxide, manganese oxide, and the like.
[0187] In a lithium-air battery or any lithium battery, lithium metal or a lithium metal alloy is a typical anode selection. Similarly, the anode of a sodium battery is usually sodium metal or a sodium metal alloy, including but not limited to alloys of antimony (Sb), tin (Sn), phosphorus (P), germanium (Ge), or lead (Pb).
[0188] The anode of a lithium-ion battery can be any suitable negative electrode active material. For example, the negative electrode active material can include a carbon-based material, a silicon-based material, a tin-based material, an antimony-based material, a lead-based material, a metal oxide (e.g., lithium or sodium metal oxide). Examples of carbon-based materials include graphite-based materials such as soft carbon, hard carbon, artificial graphite, natural graphite, a mixture of artificial graphite and natural graphite, and natural graphite coated with artificial graphite. Carbon nanotube materials can be used. Examples of silicon-based materials include silicon, silicon oxide, silicon-containing alloys, and mixtures of graphite-based materials and the above materials. Silicon oxide can be represented by SiO x (0 < x ≤ 2). The silicon-containing alloy can be, based on the total amount of the alloy, an alloy containing silicon in the maximum amount of the total metal elements (e.g., silicon, which is the metal element present in the maximum amount of all metal elements), such as an Si-Al-Fe alloy. Examples of tin-based materials include tin, tin oxide, tin-containing alloys, and mixtures of graphite-based materials and the aforementioned materials. The same applies to antimony and lead-based materials. Examples of lithium metal oxides include titanium oxide compounds such as Li4Ti5O 12 、Li2Ti6O 13 or Li2Ti3O7. Examples of sodium metal oxides include Na2Ti3O7 or Na2Ti6O 13Other metal oxides that may be mentioned herein as suitable include, but are not limited to, TiO2, Fe2O3, MoO3.
[0189] The anodes in sodium-ion batteries can be made from a variety of materials, including mixtures of activated carbon and titanium phosphate NaTi2(PO4)3, NaxC6, and hard carbon.
[0190] As an example, mesoporous carbon has been used as a cathode substrate in Li-air batteries with metal catalysts to enhance the reduction reaction rate and increase the specific capacity of the cathode. Metal catalysts used include manganese, iron, cobalt, ruthenium, platinum, silver, or mixtures of cobalt and manganese. In particular, carbon nanotube (CNT)-supported Pt catalysts (Pt / CNT) or Pt / Ir catalysts as well as other transition metal and nitrogen doped carbon phases can be used in Li-air batteries.
[0191] Aqueous Li-air batteries typically consist of an anode, an aqueous electrolyte, and a porous carbon cathode. The aqueous electrolyte combines a lithium salt dissolved in water. However, because lithium metal reacts violently with water, aqueous designs require an ion-conducting membrane divider between the lithium and the electrolyte. Hybrid Li-air battery designs have an aqueous catholyte and a non-aqueous anolyte separated by an ion-conducting membrane divider.
[0192] Typically, the active or inactive catholyte salt is a halogen (e.g., chlorine, bromine, or iodine) or a nitrate or ammonium. In certain embodiments, the active salt is a nitrate (e.g., NH4NO3) or a halide or ammonium compound, or a compound that hydrolytically dissolves in the catholyte (e.g., a compound containing a metal (e.g., AICI3)). In certain embodiments, the halide salt is an ammonium halide salt (NH4Br, NH4Cl, NHI) or a metal halide salt, where the metal can be lithium, aluminum, or titanium, or more generally an alkali metal or transition metal. Lithium chloride (pH=6) and acidic lithium chloride (pH=2) as well as LiOH (pH≈12) can be used.
[0193] The anolyte, when present, may comprise an electrolyte salt in a non-aqueous solvent, such as, for example, cyclic carbonates (propylene carbonate, ethylene carbonate, butylene carbonate, fluoroethylene carbonate, chloroethylene carbonate, vinylene carbonate, and the like); linear carbonates (dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and the like); cyclic esters (γ-butyrolactone, γ-valerolactone, and the like); linear esters (methyl formate, methyl acetate, methyl butyrate, and the like); and / or the like); tetrahydrofuran or its derivatives; ethers (1,3-dioxane, 1,4-dioxane, 1,2-dimethoxyethane, 1,4-dibutoxyethane, diglyme, tetraglyme, methyl diglyme, and the like, and / or the like); nitriles (acetonitrile, benzonitrile, and the like, and / or the like); dioxolane or its derivatives; ethylene sulfide; sulfolane; and / or sultones or its derivatives, which may be utilized alone or in mixtures of two or more. A common non-aqueous solvent is a mixture of ethylene carbonate and dimethyl carbonate.
[0194] The electrolyte salt is, for example, (a) an inorganic ion salt containing lithium (Li) such as LiClO4, LiAsF6, LiPF6, LiPF 6-x (CnF 2n+1 )x (1 < x < 6, n = 1 or 2), LiSCN, LiBr, LiCI, Li2SO4, Li2B 10 Cl 10 , Lil, LiSCN, LiPF4(C2O4), LiBF4, LiPF6 or the like, or (b) an organic ion salt containing lithium such as LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(CF3SO2)(C4F9SO2), LiC(CF3SO2)3, LiC(C2F5SO2)3, or (c) NaClO4, NaAsF6, NaPF6, NaPF 6-x (CnF 2n+1 ) x (1 < x < 6, n = 1 or 2), NaSCN, NaBr, NaI, Na2SO4, Na2B 10 Cl 10 , NaClO4, Nal, NaSCN, NaBr, NaPF4(C2O4), NaBF4, NaPF6, or the like, or (d) an organic ion salt containing sodium such as NaCF3SO3, NaN(CF3SO2)2, NaN(C2F5SO2)2, NaN(CF3SO2)(C4F9SO2), NaC(CF3SO2)3, NaC(C2F5SO2)3, or (e) (CH3)4NBF4, (CH3)4NBr, (C2H5)4NClO4, (C2H5)4NI, (C3H7)4NBr, (n-C4H9)4NClO4, (n-C4H9)4NI, (C2H5)4N - maleate, (C2H5)4N - benzoate, (C2H5)4N - phthalate, sodium stearyl sulfonate, sodium octyl sulfonate, sodium dodecylbenzenesulfonate, or the like. The ionic compound may be used alone or as a mixture of two or more. Specific electrolyte salts that can be mentioned herein are LiClO4, LiPF4(C2O4), LiBF4, LiPF6, NaClO4, NaPF4, NaBF4, and NaPF6, which can be used alone or as a mixture of two or more.
[0195] The concentration of the electrolyte salt is not particularly limited, but can be, for example, about 0.1 mol / L to about 10.0 mol / L.
[0196] The electrolyte may further include various suitable additives, such as negative electrode SEI (solid electrolyte interface) forming agents, surfactants, and the like, and / or the like. Such additives may be, for example, succinic anhydride, lithium bis(oxalato)borate, sodium bis(oxalato)borate, lithium tetrafluoroborate, sodium tetrafluoroborate dinitrile compounds, propane sultone, butane sultone, propene sultone, 3-sulfolene, fluorinated allyl ethers, fluorinated acrylates, carbonates such as vinylene carbonate, vinyl ethylene carbonate, and fluoroethylene carbonate, and / or the like.
[0197] The solid electrolyte according to the present invention can be prepared by mixing the first polymer and dopant, and optionally the second polymer, plasticizer, and other ingredients such as fillers, antioxidants, colorants, antifouling agents, and dispersants, in a solvent such as N-methyl-2-pyrrolidinone (NMP) with stirring for a period of time, typically 4-8 hours, at an elevated temperature, typically about 70°C.
[0198] When the solid electrolyte incorporates a ceramic, it can be prepared by mixing a first polymer, a dopant, optionally a second polymer, plasticizers, and other ingredients such as fillers, antioxidants, colorants, antifouling agents, and dispersants in a solvent such as N-methyl-2-pyrrolidinone (NMP) at an elevated temperature, typically about 70° C., typically for 4 to 8 hours, with stirring. After stirring for the above period, the ceramic is added and stirring is continued at an elevated temperature, typically about 70° C., for an additional period, typically 4 to 8 hours.
[0199] Mixing is performed using standard mixing techniques. For example, the polymer composition can be formed using a Banbury mixer, a Brabender mixer, and / or a twin-screw mixer. Generally, a polymer composition formed using a twin-screw extruder can exhibit better elongation and tensile properties because a twin-screw mixer provides higher shear forces during mixing.
[0200] After mixing is completed, in one embodiment, the solid electrolyte is formed into a film, for example to serve as an ion-conducting membrane divider in a battery. In one embodiment, the slurry containing the solid electrolyte is tape cast or hot pressed and cut into appropriate sizes and shapes for use in the respective energy storage system. In tape casting, the slurry containing the solid electrolyte is typically cast onto an aluminum foil and typically left to dry overnight at an elevated temperature, typically 80°C. Finally, the aluminum foil substrate is peeled off. Alternatively, hot pressing can be used instead of tape casting, which allows the amount of plasticizer to be reduced to achieve higher ceramic filler content and higher mechanical strength, if desired.
[0201] The membrane divider is disposed between the anode and the cathode to form an anode compartment and a cathode compartment. As an example, in manufacturing a battery, the electrode structure is processed to have a desired shape, such as a cylindrical, prismatic, laminated, button, and / or the like, and inserted into a container having the same shape. The ion-conducting membrane divider is inserted and secured into the container to form an anode compartment and a cathode compartment. A non-aqueous electrolyte is then injected into the anode compartment and an aqueous electrolyte is injected into the cathode compartment to produce a rechargeable lithium or sodium ion battery.
[0202] Hereinafter, the embodiments of the present invention will be described in more detail with reference to the following examples. However, the present disclosure is not limited thereto. Furthermore, what is not described in the present disclosure can be fully understood by those skilled in the art and is not exemplified in the present specification. EXAMPLES
[0203] Common methods
[0204] XRD patterns were collected using a high-resolution X-ray powder diffractometer (Bruker D8) with Cu Kα radiation (λ = 1.5406 Å) in the 2θ range of 10–100°, a nominal scan rate of 160 s / step, and a step size of 0.02°. The Generalized Structure Analysis System (AC Larson and RB Von Dreele, Los Alamos National Laboratory Report (LAUR), 2004, 86-748) was applied with a graphical user interface EXPGUI to refine the X-ray patterns. The microscopic structure of the samples was investigated using a scanning electron microscope (SEM, Zeiss Supra 40 VP). AC impedance measurements were performed using a Swagelok cell (X2 Labwares Pte Ltd) using an impedance spectrometer (Solartron SI1260, Schlumberger) in the frequency range of 0.1 Hz to 10 MHz. The cycling performance test of the lithium-air battery was carried out using a potentiostat / galvanostat (Arbin BT2000 equipped with MITS pro software).
[0205] Example 1. Preparation of LAGP ceramic pellets
[0206] Li 1+x Al x Ge 2-x (PO4)3(x=0.5) glass is prepared using a reported melt quenching method (Safanama (2014)). Further annealing at 850 °C for 2 h is performed to ensure crystallization. Based on a recent in situ synchrotron study of the LAGP phase formation process (Safanama (2016)), the annealing parameters are set to achieve high purity and ionic conductivity of the pellets.
[0207] Example 2. Characterization of LAGP ceramic pellets by X-ray powder diffraction
[0208] The Rietveld refinement (Fig. 1Aa) confirms the formation of NASICON-type LAGP as the main crystalline phase adopting the rhombohedral system (R-3c) and its association with an inevitable secondary phase of GeO2 (space group P3121) with traces of Li4P2O7 (space group P-1). The lowest activation energy E a = 0.35 eV was achieved for a sample annealed at 850 °C for 2 h, resulting in a total conductivity of 4.0 × 10 -4 S cm -1 (Fig. 1b). Annealing the sample at 850 °C reduces the mass fraction of AlPO4, another common impurity phase (as observed in Safanama (2014)) (Safanama (2016)). Refinement data also suggest that at 850 °C, aluminum clearly prefers Ge sites, and AlLi ·· The occupancy of Al becomes almost insignificant (for T = 850 °C: 0.02 Al per formula unit on 6 Li(1) sites). At lower annealing temperatures, there is a more or less random distribution of Al between the 6 Li(1) and 12 Ge sites (e.g., 0.07 Al per formula unit on Li(1) sites and 0.08 Al per formula unit on Ge sites are found in the sample annealed at 650 °C).
[0209] Example 3. Preparation of polymer membrane
[0210] Polyvinyl acetal resin, PvDF binder, plasticizer (benzyl butyl phthalate (C 19 H 20 The polymer electrolyte was prepared by mixing lithium tetrafluoroborate (LiBF4) and a dopant salt (LiBF4) at an elevated temperature of about 70 °C for 4-8 hours. After stirring was completed, the polymer electrolyte was tape-cast onto aluminum foil and dried at 80 °C overnight. The room temperature conductivity of the pure polymer phase is σtotal = 3 × 10 -6 Scm -1The Arrhenius plot of the total conductivity of the polymer electrolyte is shown in Figure 2.
[0211] The water resistance stability of the polymer components of the hybrid membrane was tested by performing DSC measurements. The results of DSC measurements (30 °C to 250 °C) of the hybrid membrane after immersion in deionized water for about one week are shown in Figure 3. The only peaks that can be observed belong to the endothermic melting peaks of BUTVAR B98 (Eastman Chemical Company) and PVDF at 60 °C and 150 °C, respectively. No signs of water absorption in the membrane are observed.
[0212] Example 4. Preparation of LAGP ceramic-organic polymer membranes
[0213] LAGP ceramic-organic polymer films are made using the plasticizer benzyl butyl phthalate (C 19 H 20 O4), polyvinyl butyral resin ((C8H 14 O2) n), lithium tetrafluoroborate (LiBF4) as the dopant salt, and polyvinylidene fluoride dimer binder (PVDF) as the fast ion conducting ceramic filler in a polymer blend. The LAGP ceramics are made by reported methods (Safanama (2014) and Safanama (2016)). BUTVAR B98 (Eastman Chemical Company), a type of polyvinyl butyral resin with excellent binding efficiency, is reported to be stable in both acidic and basic solutions. BUTVAR B98 typically has a molecular weight of 40,000-70,000, a hydroxyl content of 18.0-20.0%, an acetate content of up to 2.5%, and a butyral content of about 80%. The stability of this resin was tested in both weak and strong bases and acids by ASTM method D543-56T to show its excellent resistance (Eastman Chemical Company, Butvar, polyvinyl butyral resin: Properties and uses; M. Bolgar, J. Hubball, J. Groeger and S. Meronek, Handbook for the Chemical Analysis of Plastic and Polymer Additives, CRC Press, 2007). It was selected as one of the main components of this method. To improve flexibility, this method used benzyl butyl phthalate (C 19 H 20 O4) was used. N-methyl-2-pyrrolidinone (NMP) was used as the solvent.
[0214] In one embodiment of the membrane system, the weight percentages of the components are as follows: 81 wt% LAGP, 3 wt% benzyl butyl phthalate, 4 wt% polyvinyl butyral resin, 4 wt% LiBF4, and 8 wt% PVDF. The ideal amount of solvent NMP is 3.5 ml for 1 g of LAGP ceramic. The synthesis has been successfully scaled up to 5 g. The preparation of the above method involves mixing the components in a glass beaker at 70°C using a magnetic stirrer. After stirring for 6 hours, the mixture was cast onto aluminum foil and dried overnight at 80°C. This tape casting can be easily scaled to large dimensions without compromising the homogeneity, thickness, and performance of the membrane.
[0215] The mechanical properties and ionic conductivity of the membrane were optimized by varying the mass fraction of the ceramic and polymer components, thereby achieving a conductivity of 1.0 × 10 -4 S cm -1 A product with a total conductivity of was obtained (Figure 4a). It should be noted that this value is almost an order of magnitude lower than the previously published PEO-based hybrid membranes (Safanama (2014)), but the conductivity value is still acceptable for application as an anode protective membrane in Li-air batteries.
[0216] Example 5. Characterization of LAGP ceramic-organic polymer films
[0217] As shown in Figure 4b, the refined Rietveld pattern of the film shows LAGP (space group R-3c) as the main crystalline phase. The lattice parameters of the main crystalline phase of LAGP in the film are a = 8.2614(2) Å and c = 20.636(1) Å, which are only slightly lower than the value of c = 20.6501(1) Å for the LAGP phase in pellet form, respectively. This confirms that the slurry preparation does not cause a phase transition in the main crystalline phase.
[0218] Example 6. Preparation of garnet-type ceramic-organic polymer films
[0219] Doped Li garnet oxides 7-x La3Zr2O12 Specifically, Ta and Ga co-doped Li 6.75 La3Zr 1.75 Ta 0.25 O 12 Ga 0.05 was used as a ceramic filler in a polymer matrix containing BUTVAR B98, PVDF, and benzyl butyl phthalate variously doped with LiBF4, LiTFSi, and LiCl. In addition, SOLSPERSE 20,000 was used as a dispersing agent. The components were mixed manually and then pressed using a hot press to form a thin layer of thin film. Ta, Ga co-doped Li in hybrid films 6.75 La3Zr 1.75 Ta 0.25 O 12 Ga 0.05 Use of Ta, Ga co-doped Li 6.75 La3Zr 1.75 Ta 0.25 O 12 Ga 0.05 is 7x10 -5 Scm -1 (note that the ionic conductivity of 10.5x10 is 5.4x10) -5 Scm -1 (FIG. 5). After comparing LiBF4, LiTFSi, and LiCl as doping salts, LiCl appeared to be the most suitable for films with garnet-type fillers.
[0220] Example 7. Stability of LAGP ceramic-organic polymer membranes in LiCl solutions of different pH
[0221] As a measure of chemical stability, the hybrid membranes were immersed in different catholyte solutions with different pH values for different times. The effect of immersion time on the crystal structure, ionic conductivity, and surface topography of the hybrid membranes was investigated.
[0222] Crystal structure
[0223] Figure 6a compares the XRD patterns of the hybrid membrane before and after immersion in a slightly acidic LiCl solution (10 M; pH 5-6). Interestingly, the XRD patterns are nearly identical and no impurity peaks are formed over long immersion times. This translates into excellent stability of the hybrid membrane in neutral LiCl solution (10 M). To investigate in more detail the slight changes in the phase fraction and lattice constant of the main LAGP phase with immersion time, the Rietveld refinement patterns are compared and the results are summarized in Table 1. Thus, both the lattice constants a and c remain nearly constant for almost 6 months of immersion, and the phase fraction of the LAGP phase decreases only slightly. This indicates that the membrane exhibits high chemical stability when in contact with LiCl (10 M) for up to 6 months.
[0224] Further investigation of the chemical stability was carried out in a more corrosive catholyte solution of strongly acidified LiCl (10 M) with pH values ranging from 2 to 3. The membrane is able to withstand the attack from the acid. The XRD pattern after immersion did not change as shown in Figure 6b. Hence, there is no sign of decomposition for this hybrid membrane in contact with this catholyte solution. As summarized in Table 1, the Rietveld refinement of the XRD data shows that after one month of immersion, the phase fraction of the LAGP phase decreases only slightly from 97 to 94.4, resulting in a slight separation of a second phase of GeO2. Extraction of Ge from the main LAGP phase is evident from the constant increase in the proportion of the GeO2 phase. As expected, the changes in the lattice constants a and c are slightly more pronounced for the more severe acidic solutions. A sharp decrease occurs for the lattice constant c over the first 7 days of immersion, followed by a smaller rate of decrease with subsequent immersion.
[0225] [Table 1]
[0226] Ionic Conductivity
[0227] As shown in Figure 7, in LiCl (10 M), the resistance decreased with immersion time, and therefore the conductivity increased. This decrease in resistance could be attributed to the formation of new amorphous phases in the structure. Another possibility is the gradual increase in salt doping of the polymer components by LiCl from the concentrated solution. The same trend was observed for LATP immersion in lithium chloride, justified by the formation of LiCl-xH2O with lower resistance at the grain boundaries (K. Takahashi (2012), M. Zhang (2012)).
[0228] Surface Topography
[0229] SEM images of the hybrid membrane before and after immersion are shown in Figure 8. While the detailed morphology of the membrane gradually evolves over this long period, there is no sign of holes penetrating the membrane formed upon prolonged exposure to this catholyte. The polymer layer formed on the surface of the membrane may be one of the factors contributing to improving the stability of the membrane by protecting the layers underneath.
[0230] Example 8. Cycling performance of LAB containing LAGP ceramic-organic polymer membrane in LiCl solutions of different pH
[0231] This high stability of the proposed hybrid membrane translates directly into a high-performance energy storage system with longer cycle life when compared to systems using conventional composite membranes. As an example, Figure 9a and Figure 9b represent the room temperature discharge / charge profiles of an aqueous Li-air battery with the hybrid membrane and LiCl (10 M) at pH 6.0 and acidified LiCl at pH 2 as catholyte solutions, respectively. To improve the contact, a drop of LiPF6 in EC-DMC is used on the lithium anode. The reduction and evolution of oxygen is catalyzed using a CNT / Pt air cathode. In both cases, each cycle is limited to 1 h and the current density is 0.03 mA cm in the voltage range of 2–4.5 V. -2The charge / discharge capacity of the battery was intentionally limited to 50 mAh / gC in this test. In neutral LiCl (10M), the cell operated at low overpotential for more than 80 cycles (Figure 9a) until the overpotential gradually increased. Note that organic lithium-air batteries typically have a 10 times larger overpotential (hence lower power capability as well as lower energy efficiency).
[0232] The superior performance of the new hybrid membrane is demonstrated in a Li-air battery utilizing highly acidified LiCl (10 M) at pH 2 (Figure 9b). Under these acidic conditions, conventional PEO-based membranes decompose within a few hours. As can be seen, the cell operates with a low overpotential of <0.4 V for most of the cycles. The aqueous Li-air battery was operated for more than 140 cycles, with each cycle limited to 1 hour. The charge-discharge curves show a flat plateau for most of the cycles. The relatively low equilibrium voltage of the battery can be justified by assuming that the battery reaction essentially follows a two-electron mechanism, both during charging and discharging. Figure 9c compares the overpotential for the hybrid membrane presented here with the PEO-based hybrid membrane in an aqueous Li-air battery. As can be seen, the higher conductivity (8 × 10) of the PEO-based membrane results in a significant improvement in the overpotential of the PEO-based membrane. -4 S cm -1 ), the overpotential is initially smaller when compared to the hybrid membrane of the present invention. However, the use of the hybrid membrane significantly increases the battery life.
[0233] References
[0234] The references cited herein are listed on the following pages and are incorporated herein by reference.
[0235] [Non-Patent Document 1] Journal of Materials Chemistry A, 2016, 4, 7718-7726, D. Safanama, N. Sharma, RP Rae, HEA Brand and S. Adams.
[0236]
Outdoor Tool2
[0237]
Outdoor Tools3
[0238]
Outdoor Tools 4
[0239]
Direct Environment 5
[0240]
Non-licensed Document 6
[0241]
Non-licensed Document 7
[0242]
Non-licensed Document 8
[0243]
Non-licensed literature 9
[0244]
Non-licensed literature 10
Claims
1. 1. A solid electrolyte comprising a first polymer selected from one or more of the group consisting of polyvinyl acetal, polyvinyl acetate, and copolymers comprising vinyl acetal and / or vinyl acetate units, and a dopant comprising a lithium salt or a sodium salt.
2. 2. The solid electrolyte of claim 1, wherein the polyvinyl acetal comprises units having the formula (I). 【Chemistry 1】 In the formula, R 1 and R 2 is independently selected from hydrogen, alkyl or alkyl substituted with hydroxyl, thiol, amino, halo, nitro, alkoxy, thioalkyl, alkylamino, dialkylamino, carboxy, alkoxycarbonyl, carbamoyl, thiocarbamoyl, alkylcarbamoyl, alkylthiocarbamoyl, dialkylcarbamoyl, or dialkylthiocarbamoyl; and R 3 is selected from hydrogen, alkyl or alkyl substituted with hydroxyl, thiol, amino, halo, nitro, alkoxy, thioalkyl, alkylamino, dialkylamino, carboxy, alkoxycarbonyl, carbamoyl, thiocarbamoyl, alkylcarbamoyl, alkylthiocarbamoyl, dialkylcarbamoyl, or dialkylthiocarbamoyl.
3. 2. The solid electrolyte of claim 1, wherein the first polymer is a copolymer comprising vinyl acetal units and units selected from one or more of the group consisting of vinyl acetate units, vinyl alcohol units, (meth)acrylic acid units, and methyl (meth)acrylate units.
4. 4. The solid electrolyte of claim 3, wherein the first polymer is a copolymer of vinyl acetal, vinyl acetate and vinyl alcohol units.
5. 10. The solid electrolyte of claim 1, wherein the first polymer is polyvinyl butyral.
6. 2. The solid electrolyte of claim 1, further comprising a second polymer selected from one or more of the group consisting of polyvinylidene difluoride (PVDF), polyvinyl alcohol, polyolefin-based resins, poly(propylene carbonate) polyester-based resins, tetrafluoroethylene, vinylidene difluoride-hexafluoropropylene copolymers, vinylidene difluoride-perfluorovinyl ether copolymers, vinylidene difluoride-tetrafluoroethylene copolymers, vinylidene difluoride-trifluoroethylene copolymers, vinylidene difluoride-fluoroethylene copolymers, vinylidene difluoride-hexafluoroacetone copolymers, vinylidene difluoride-ethylene copolymers, vinylidene difluoride-propylene copolymers, vinylidene difluoride-trifluoropropylene copolymers, vinylidene difluoride-tetrafluoroethylene-hexafluoropropylene copolymers, and vinylidene difluoride-ethylene-tetrafluoroethylene copolymers.
7. 10. The solid electrolyte of claim 1, further comprising a plasticizer selected from one or more of the group consisting of phthalate esters, phosphate ester plasticizers, phosphoric acid esters, fatty acid esters, esters of azelaic acid, sebacic acid esters, trimellitic acid esters, and polymeric plasticizers.
8. The dopant is lithium perchlorate (LiClO 4 ), lithium tetrafluoroborate (LiBF 4 ), lithium hexafluorophosphate (LiPF 6 ), lithium bis(trifluoromethanesulfonyl)imide, lithium bis(trifluoromethane)sulfonimide (Li[N(CF 3 SO 2 ) 2 ]), lithium hexafluoroarsenate(V) (LiAsF 6 ) Lithium bis(oxalatoborate), Lithium nitrate (LiNO 3 2. The solid electrolyte of claim 1, wherein the lithium salt is selected from one or more of the group consisting of lithium chloride (LiCl) and lithium bromide (LiBr).
9. The dopant is sodium nitrate (NaNO 3 ), sodium perchlorate (NaClO 4 ), sodium tetrafluoroborate (NaBF 4 ), sodium hexafluorophosphate (NaPF 6 ) Sodium bis(trifluoromethanesulfonyl)imide, sodium bis(trifluoromethane)sulfonimide (Na[N(CF 3 SO 2 ) 2 ])Na[N(CF 3 SO 2 ) 2 ], sodium hexafluoroarsenate(V) (NaAsF 6 2. The solid electrolyte of claim 1, wherein the sodium salt is selected from one or more of the group consisting of sodium bis(oxalatoborate), sodium halides, sodium thiocyanate (NaSCN), sodium pentacyanopropenide, sodium tetracyanopyrrolate, and sodium tricyanoimidazolate.
10. 10. The solid electrolyte of claim 1 further comprising a lithium ion conducting ceramic or a sodium ion conducting ceramic.
11. Lithium ion conductive ceramics include NASICON type ceramics, lithium-filled garnet type oxides, LISICON type ceramics, perovskite type oxides, Li 3 PO 4 -Li 4 SiO 4 Pseudo-binary system Li 3+x (P 1-x S x )O 4 and lithium ion conducting oxyhalide glasses.
12. The sodium ion conducting ceramic oxides include NASICON structure oxides, beta-alumina and beta''-alumina phase Na 2 O・nAl 2 O 3 11, 5≦n≦11, rare earth sodium silicates, and sodium ion conducting oxyhalide glasses.
13. 10. The solid electrolyte of claim 1, optionally further comprising a first polymer present in an amount of 5-30% by weight, and a lithium or sodium salt present in an amount of 15-30% by weight, and a second polymer present in an amount of 30-50% by weight, and / or a plasticizer present in an amount of 10-25% by weight.
14. 14. The solid electrolyte of claim 13, wherein the solid electrolyte comprises 10-25 wt.% plasticizer, 15-30 wt.% polyvinyl acetal, 15-30 wt.% lithium or sodium salt, and 30-50 wt.% PvDF.
15. 11. The solid electrolyte of claim 10, wherein the ceramic is present in an amount of from 60% to 90% by weight.
16. 16. The solid electrolyte of claim 15 comprising 60-90 wt.% of a fast lithium ion conducting ceramic, 1-5 wt.% of a plasticizer, 2-8 wt.% of a polyvinyl acetal, 2-8 wt.% of a lithium salt, and 4-15 wt.% of PvDF.
17. 16. The solid electrolyte of claim 15 comprising 60-90 wt.% of garnet-related type Ta and Ga co-doped lithium lanthanum zirconate, 2-8 wt.% of plasticizer, 2-8 wt.% of polyvinyl acetal, 2-8 wt.% of lithium salt, and 4-15 wt.% of PVDF.
18. 13. An ionically conductive membrane divider for use in a battery comprising the solid electrolyte of claim 1.
19. 20. A battery comprising an anode, a cathode, a catholyte, and optionally an anolyte, the ion-conducting membrane divider of claim 18 separating the catholyte from the cathode.
20. a) providing a solid electrolyte according to claim 1, and b) Forming the solid electrolyte into a membrane A method for making an ion-conducting membrane divider suitable for use in a battery, comprising the steps of:
Citation Information
Cited By
Ultrasonic sensor and vehicle
CN122506567A
Ultrasonic sensor and vehicle
DE102026104134A1